The occurrence of microplastics in farmland and grassland soils in the Qinghai-Tibet plateau: Different land use and mulching time in facility agriculture. (15th June 2021) - Feng, Sansan; Lu, Hongwei; Liu, Yunlong
Abstract: Microplastic (MP) pollution in the environment has aroused great concern. However, our knowledge of MP abundance and distribution in soil environment is scarce. This work investigated the MPs in the farmland and grassland at a remote area of China, namely, the eastern area of the Qinghai–Tibet Plateau (QTP). The average numbers of MPs were 53.2 ± 29.7 and 43.9 ± 22.3 items/kg in shallow and deep soil, respectively, from 35 soil samples. A remarkable difference in MP abundances was observed among soil samples from mulch farmland, greenhouses, farmland without covering, and grassland. The MPs were mostly in the form of a film and transparent in color in this study. The dominant polymers of MPs in the soil samples were polyester (PE) and polypropylene (PP). This study revealed the characteristics of MP distribution among different land use at the QTP, and MPs may stem from the fragmentation of plastic mulch in farmland soil. Notably, MP abundance increased with the increase in mulching time in facility agriculture. Additionally, human disturbances and increased mulching time in facility agriculture promote the fragmentation of soil MPs. This study provides important data for follow-up research on MPs in a plateau terrestrial ecosystem. Graphical abstract: Image 1 Highlights: Soil MPs with different land use and mulching time were studied simultaneously. The major MP source was the application of plastic mulch in farmlands. MPs will accumulate with the increase in mulching time in facility agriculture. Extending the mulching time in facility agriculture promotes MP degradation.